METHODOLOGICAL PROBLEMS WITH EVALUATING CHANGE EFFICIENCY - Jerzy Paszkowski (Institute of Economic Research (IER), 2017)
Research background: Changes result from a turbulent environment and internal situation of an organization. Rarely do changes happen spontaneously, usually they stem from decisions consciously shaped and taken by the management. Both the reasons as well as consequences of changes appear on multiple grounds and areas, often strongly interrelated. This leads to far-reaching consequences, mainly difficulties in practical operations as well as consequences for studies, analyses and related scientific generalizations and the conclusion-drawing process in both domains. Purpose of the article: Purpose of this article is to present and make a critical analysis of the existing achievements in the area of evaluating change efficiency, and indicate opportunities and difficulties in formulating new, in particular synthetic, indicators of change efficiency. Methodology/methods: Methodology applied in this paper is hypothetical and deductive. Findings & Value added: Managers need synthetic measures that are hard to develop. Various methods may be used in order to do it, starting from simple and complex point scales and ending up with methods applied in other sciences, e.g. the Geneva method or its variations applied to evaluate the standard of living and development. Still this requires the isolation of main analytical measures, their upper and lower thresholds, in subsequent change or process areas, and the application of statistical methods to calculate change status or effect. Such action requires longer change planning and preparation, readiness on the part of the managerial staff, and continuous monitoring with active participation of leaders and change managers.
Keywords: A11; B16; G34; D61; 330; change; efficiency evaluation; analytical and synthetic measures of change evaluation